800 solved problems in Vector mechanics for engineers - Shelley, Joseph F. (McGraw-Hill, 1990)
This is a complete and expert source of problems with solutions in Vector mechanics for Engineers for 2nd-year college and university engineering students to cover all aspects of the basic course. This is the comprehensive solved-problem reference in the subject. It provides the student with all the problem solving drill ever needed, all in one book. There is no expository text. A course in engineering mechanics is required of all engineering students.